Does global warming affect dream content?: analyzing a 30-yr. dream series - Schredl, Michael (International journal of dream research, 2021)
The continuity hypothesis of dreaming postulates that dreams reflect waking life, e.g. preoccupations, experiences, thoughts; however, other topics like seasonal changes have been studied very rarely. A long dream series recorded between 1984 and 2015 (over 30 years) including 11,808 dreams showed that “cold” elements like snow, ice, and hail occurred less often over time and, thus, indicates that dreams might provide clues regarding global changes. Using modern tools for digital dream content analysis might enable researchers to validate this preliminary finding using other large data sets.